Monkeying Around: Using Non-human Primate Models to Study NK Cell Biology in HIV Infections - Manickam, Cordelia; Shah, Spandan V.; Nohara, Junsuke; Ferrari, Guido; Reeves, R. Keith (Frontiers in Immunology, 2019)
Natural killer (NK) cells are the major innate effectors primed to eliminate virus-infected and tumor or neoplastic cells. Recent studies also suggest nuances in phenotypic and functional characteristics among NK cell subsets may further permit execution of regulatory and adaptive roles. Animal models, particularly non-human primate (NHP) models, are critical for characterizing NK cell biology in disease and under homeostatic conditions. In HIV infection, NK cells mediate multiple antiviral functions via upregulation of activating receptors, inflammatory cytokine secretion, antibody dependent cell cytotoxicity through antibody Fc-FcR interaction and others. However, HIV infection can also reciprocally modulate NK cells directly or indirectly leading to impaired/ineffective NK cell responses. In this review, we will describe multiple aspects of NK cell biology in HIV/SIV infections and their association with viral control and disease progression, and how NHP models were critical in detailing each finding. Further, we will discuss the effect of NK cell depletion in SIV-infected NHP and the characteristics of newly described memory NK cells in NHP models and different mouse strains. Overall, we propose that the role of NK cells in controlling viral infections still remains incompletely understood and that NHP models are indispensable in order to efficiently address these deficits.